The present status and future potential of snap beans in China - Henry, Guy; Peihua, L (International Center for Tropical Agriculture, 1989)
An overview is given of the current status of snap bean cultivation in China, where production estimates for 1988 range from 2.5 to 5.0 million MT. Historical aspects of Chinese agriculture, and vegetable cultivation in particular, are briefly discussed. Highly specialized agronomic techniques used are seedling transplanting, optimal use of climbing var., bed culture, intercropping, mulching, fertilization, and use of hybrid seed. Approximate production costs and marketing and consumption aspects of snap beans in the country are also reviewed. Likewise, present constraints and future potential of snap beans are analyzed. Data indicate that snap beans do have a significant potential. Recommendations are to expand vegetable crop area (possibly in the north and NE), study the effectiveness of current pest and disease management practices and propose alternative ones, introduce earlier maturing var., and develop techniques to improve the storability of this vegetable. (CIAT)